Investigation on mechanical and modal properties of aluminium based fibre metal laminates - Mohamad Nazirul Mubin, Merzuki (2020)
The combination of materials between metal alloys and composite materials has been used for thousands of years to reach better performance requirement. To achieve the best combination of material properties and service performance, a study on the dynamic behaviour is one of the main points to be considered. Besides, it is important to investigate the natural frequency and the possible mode shape of the selected of the materials to avoid problems related to vibrations. This master project was aimed to investigate the mechanical properties of aluminium alloys and composite materials. At the same time, the dynamic behaviour of combination between aluminium alloys (Al 2024-T0) and three different composite materials (CFRP, GFRP, UD-CFP) by free vibration test also evaluated. Compression moulding technique was used to fabricate the fibre metal laminate (FML) plates. The fabrication method was according to ASTM D3039 standard and mechanical properties of the plate were determined from the tensile test method. Variation of natural frequency and mode shape of FML based on the aluminium alloys (Al 2024-T0) and three different composite materials were evaluated through different configuration lay-up of 2/1 and 3/2 stacking sequences with multiple boundary conditions. Based on E756 standard, modal testing using impact hammer with roving accelerometer method was carried on to the specimens. Finite element analysis (FEA) models by using commercial ABAQUS software was used to determine natural frequency and mode shape. The experimental results from modal testing were then compared with the FEA values. It was found that, the natural frequency of the FMLs plates increased when more Al layers were embedded in the composite layers. The results reveal that a percentage increase in natural frequency from 29.41 % to 71.98 %. Meanwhile, the percentage increment in natural frequency was from 54.36 % to 88.53 % between fixedfree and fixed-fixed boundary conditions. The vibration analysis of FML plates were validated, where the percentage error between numerical analysis and experimental results are observed to be 0.08 % to 16.17 %. In conclusion, with the presence of aluminium alloy plates in the composite layers, the natural frequency will increase as the value of stiffness increase. The boundary conditions significantly affected the natural frequency of FML plates because of the restraint effect at the edges.